Whole-grain food consumption in Singaporean children aged 6–12 years - Jia En Neo; Saihah Binte Mohamed Salleh; Yun Xuan Toh; Kesslyn Yan Ling How; Mervin Tee; Kay Mann; Sinead Hopkins; Frank Thielecke; Chris J. Seal; Iain A. Brownlee (Journal of Nutritional Science, 2016)
Public health bodies in many countries are attempting to increase population-wide habitual consumption of whole grains. Limited data on dietary habits exist in Singaporean children. The present study therefore aimed to assess whole grain consumption patterns in Singaporean children and compare these with dietary intake, physical activity and health parameters. Dietary intake (assessed by duplicate, multipass, 24-h food recalls), physical activity (by questionnaire) and anthropometric measurements were collected from a cross-section of 561 Singaporean children aged 6–12 years. Intake of whole grains was evaluated using estimates of portion size and international food composition data. Only 38·3 % of participants reported consuming whole grains during the dietary data collection days. Median intake of whole grains in consumers was 15·3 (interquartile range 5·4–34·8) g/d. The most commonly consumed whole-grain food groups were rice (29·5 %), wholemeal bread (28·9 %) and ready-to-eat breakfast cereals (18·8 %). A significantly lower proportion of Malay children (seven out of fifty-eight; P < 0·0001) consumed whole grains than children of other ethnicities. Only 6 % of all children consumed the amount of whole grains most commonly associated with improved health outcomes (48 g/d). There was no relationship between whole grain consumption patterns and BMI, waist circumference or physical activity but higher whole grain intake was associated with increased fruit, vegetable and dairy product consumption (P < 0·001). These findings demonstrate that consumption of whole grain foods is low at a population level and infrequent in Singaporean children. Future drives to increase whole-grain food consumption in this population are likely to require input from multiple stakeholders.